well...
you have two choices. One, just treat the fractions like normal numbers:
x - 1/3 = -25/3
x - 1/3 (+ 1/3) = -25/3 (+ 1/3)
x = -24/3
x = -8
or, you could get rid of the fractions by multiplying by the LCD, in this case, 3:
(x - 1/3) * 3 = (-25/3) * 3
3x - 1 = -25
3x - 1 + 1 = -25 + 1
3x = -24
3x/3 = -24/3
x = -8
Hope this helps :)
2006-12-03 13:19:49
·
answer #1
·
answered by disposable_hero_too 6
·
0⤊
1⤋
FIRST the reason; i will substitute - 3 / 5 for x in the unique equation and notice if the two sides of the = are certainly equivalent -3/5/ (-3/5 + a million) = ( 3/ (2 x -3/5)) + a million -3/5/2/5 = ( 3/ - 6/5) + a million -3/2 = ( 15/ -6) + a million -5/2 = ( -15/ 6) DIVIDE by employing 3/3 = -5/2 the respond is stable AND -5/2 = - 2.5 suggestion; in case you have fraction difficulty, use a calculator that provides decimal effects to transform all fractions to decimal . Sorry I had no room to describe all yet between the regulations/steps
2016-10-13 23:02:08
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
x = -25/3 + 1/3
= -24/3
2006-12-03 13:20:49
·
answer #3
·
answered by Rajkiran 3
·
0⤊
0⤋
x - 1/3 = -25/3
You wnat to first clear the denominators of the fractions by multiplying both sides of the equation by their LCD. Here the denominators are the same, so multiply by 3.
3(x - 1/3) = - 3(25/3)
3x - 1 = - 25
And the rest you have done before
2006-12-03 13:20:06
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
to add fractions with the same denominator just add their numerators. (e.g. 5/4 + 2/4 = 7/4).
If their denominators are different mutiply one fraction numerator and denominator by the other one. E.G.:
3/5 + 4/7 =
(3/5)7 + (4/7)5 =
21/35 + 20/35=
41/35
The answer to your problem should be x = 24/3.
2006-12-03 13:22:09
·
answer #5
·
answered by Scooter_MacGyver 3
·
0⤊
0⤋
get rid of the fractions if you can.
3(x-1/3=-25/3)
3x-1=-25
3x= -24
x= -8
2006-12-03 13:21:59
·
answer #6
·
answered by jekelly90 2
·
0⤊
0⤋
x = -8
2006-12-03 13:20:16
·
answer #7
·
answered by Mayur 2
·
0⤊
0⤋